2008
DOI: 10.4103/0019-509x.41772
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprofile of Hodgkin′s lymphoma in India

Abstract: AIMS AND BACKGROUND: The immunoprofi le of the Reed Sternberg cell with respect to immunoreactivity for CD20 and lack of CD15 has been described as a poor prognostic factor. Large scale studies analyzing the immunoprofi le of Hodgkin's lymphoma (HL) from India are lacking. The aim of this study was to obtain baseline information on relative frequencies and immunoprofi les of the two major types of HL and comparing reports from developed and developing countries. MATERIALS AND METHODS: 451 cases of HL were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
1
13
2
Order By: Relevance
“…Similar to our low frequency (43%) of CD15 expression in CHL, in a cohort of 397 cases of CHL from India, only 49% cases were immune-reactive for CD15 (from Dako, for non-sialylated form) 10. In a small series (33 cases) of CHL from Taiwan, Chang et al 11 reported that CD15 (Clone C3-D1, DAKO, for non-sialylated CD15) was expressed in 71% cases.…”
supporting
confidence: 83%
“…Similar to our low frequency (43%) of CD15 expression in CHL, in a cohort of 397 cases of CHL from India, only 49% cases were immune-reactive for CD15 (from Dako, for non-sialylated form) 10. In a small series (33 cases) of CHL from Taiwan, Chang et al 11 reported that CD15 (Clone C3-D1, DAKO, for non-sialylated CD15) was expressed in 71% cases.…”
supporting
confidence: 83%
“…This rate of 31 % is similar to the 30% seen in west [1] and appears to be within the range reported from surrounding Eastern Mediterranean countries as well as India where rates varied from 21.6% in Jordan to 41% in UAE. [18][19][20][21][22][23][24] These findings contrast with the much lower frequency in East Asian countries such as Japan where HL constitutes only 7% of ML in a recent large study. [4] The most frequent histological subtype of HL in the current study was NS, which is different from earlier reports from Iraq, [10,11] and some earlier reports from nearby countries and India, [6,19,[22][23][24][25] in which the mixed cellularity subtype was the most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] These findings contrast with the much lower frequency in East Asian countries such as Japan where HL constitutes only 7% of ML in a recent large study. [4] The most frequent histological subtype of HL in the current study was NS, which is different from earlier reports from Iraq, [10,11] and some earlier reports from nearby countries and India, [6,19,[22][23][24][25] in which the mixed cellularity subtype was the most frequent. This changing pattern is consistent with more recent reports from Saudi Arabia, Jordan, UAE and Kuwait, where higher relative rates of NS HL were reported approaching those seen in the United States and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed cellular and nodular sclerosis types is the most common HL sub types in the reviewed countries. In the Sri Lankan sample, Pakistan and India the commonest HL sub type was mixed cellular, where as in the USA and Japan the commonest was nodular sclerosis type [5,8,9,10].…”
Section: Discussionmentioning
confidence: 99%